Dental management of a child with EEC syndrome - (:unkn) unknown (My University, 1992)
The EEC syndrome is a condition characterized by ectrodactyly, ectodermal dysplasia and clefting of the lip and/or palate. Here we report a case of a boy with the EEC syndrome. The clinical and radiologic aspects of this condition, as well as the dental treatment, are reviewed.
Keywords: Humans; Syndrome; Male; Child; Anodontia; Cleft Lip; Cleft Palate; Abnormalities, Multiple; Ectodermal Dysplasia; Dental Care for Disabled; Foot Deformities, Congenital; Hand Deformities, Congenital; Pedigree